Changes in the Care of Neurological Diseases During the First Wave of the COVID-19 Pandemic: A Single Private Center Study in Argentina - Calandri, Ismael L.; Hawkes, Maximiliano A.; Marrodan, Mariano; Ameriso, Sebastián F.; Correale, Jorge; Allegri, Ricardo F. (Frontiers in Neurology, 2021)
Introduction: Healthcare systems are struggling to cope with the rapid evolution of the COVID-19 pandemic. In Argentina, the pandemic is advancing despite prolonged lockdown measures. We aim to analyze the impact of the easing of lockdown measures in the number of visits to the emergency department (ED), and outpatient consultations (OC) to a tertiary neurological center. Methods: We compared the number of ED visits with the social mobility overtime. We also compared the number of OC, and the geographic distribution of patients' addresses between 2019 and 2020. Results: ED visits decreased 48.33% (n = 14,697 in 2019 vs. n = 7,595 in 2020). At the beginning of the lockdown, the social mobility decreased in pharmacies/groceries, and workplaces, along with a reduction in the number of ED visits. With the easing of lockdown restrictions, the social mobility decreased in residential places, slightly increased in workplaces and almost return to normal in pharmacies/groceries. Variations in ED visits correlate better with social mobility in workplaces (coef. =0.75, p < 0.001) than in groceries/pharmacies (coef. =0.68, p < 0.001). OC decreased 43%. Fourteen percent of OC were tele consults. This was associated with an increase of the geographical area of influence of our center (standard distance of 109 km in 2019 and 127 km in 2020). Conclusions: Despite an increase in social mobility, the number of ED visits and OC to an Argentinian tertiary neurological center remain worrisomely low. The pandemic catalyzed the introduction of telemedicine in our country. This has also allowed patients from distant zones to gain access to specialized neurological care.